An environmentally friendly material for automotive interior and exterior trim and its preparation method

CN122978593APending Publication Date: 2026-10-27JIANGSU HUAPIN BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611264390.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

这不仅会引起汽车内外饰件表面褪色、粉化、开裂,还会导致力学性能断崖式下降

Benefits of technology

本发明构建了内源抗氧和外源抗紫的双效化学防护体系,提升了材料的耐候性。通过碱木质素与纳米纤维素的杂化改性,利用了木质素分子骨架中富含酚羟基的抗氧化和紫外线吸收特性,将其作为自由基猝灭剂;同时配合负载于介孔二氧化硅中的受阻胺光稳定剂HALS-944作为外源抗紫剂。两者在聚丙烯基体中形成的化学协同,能够长效、持续地消耗光氧老化过程中产生的游离基,有效阻断聚丙烯及植物纤维大分子链的断裂反应,解决了传统环保复合材料在户外暴晒或车内高温环境下极易发生的力学性能降低的技术难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978593A_ABST
    Figure CN122978593A_ABST
Patent Text Reader

Abstract

This invention relates to the field of polypropylene technology, specifically to an environmentally friendly material for automotive interior and exterior trim, and its preparation method. This invention overcomes the technical problem of poor weather resistance in existing environmentally friendly polypropylene materials. The invention involves mixing polypropylene, POE, a modifier / reinforcing agent, a modified light stabilizer, and additives; granulating the mixture using a twin-screw extrusion assisted by supercritical carbon dioxide and vacuum devolatilization; and then performing asymmetric temperature-controlled injection molding with rapid cooling in the fixed mold and slow cooling in the moving mold to obtain the environmentally friendly material. This invention achieves excellent weather resistance and mechanical properties through the synergistic effect of endogenous natural antioxidants and exogenous UV resistance, dense surface crystallization barrier, and supercritical low-temperature processing.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of polypropylene, in particular to an environmentally friendly material for automotive interior and exterior and a preparation method thereof. BACKGROUND

[0002] With the development of global automobile industry towards light weight and green, environmentally friendly materials for automotive interior and exterior have become the focus of major automobile manufacturers and material research institutions. Among many base resins, polypropylene is widely used in automotive instrument panels, door interior panels, bumpers and exterior pillars due to its low density, good processing performance, easy recycling and excellent comprehensive mechanical properties. In order to meet the increasingly stringent environmental requirements, in recent years, natural plant fibers, bio-based resins or industrial by-products (such as lignin) are often used to replace traditional talc or glass fibers as reinforcing fillers for polypropylene to significantly reduce the carbon footprint of the material.

[0003] However, the existing polypropylene-based environmentally friendly composite materials still face serious technical problems in practical application, the most prominent of which is poor weather resistance. Because the polypropylene molecular chain itself contains active tertiary carbon atoms, combined with the introduction of natural bio-based materials (such as plant fibers, bamboo powder, etc.) rich in hemicellulose which is prone to photodegradation and thermal oxidative aging, the material is prone to macromolecular chain scission under long-term ultraviolet radiation, alternating temperature and humidity outdoors and high temperature in the car. This not only causes the surface of automotive interior and exterior parts to fade, powder and crack, but also causes a sharp decline in mechanical properties. In addition, in order to compensate for weather resistance, a large amount of small molecule antioxidants and light stabilizers are often simply and roughly added in traditional processes, which easily precipitates (blooming) at high temperatures, thereby causing serious VOC release and odor problems in the car. Therefore, how to solve the problem of poor weather resistance of environmentally friendly materials through the deep integration of materials and processes is a technical bottleneck that needs to be broken through at present.

[0004] Therefore, an environmentally friendly material for automotive interior and exterior and a preparation method thereof are provided. SUMMARY

[0005] The present application aims to design an environmentally friendly material for automotive interior and exterior and a preparation method thereof. The present application mixes polypropylene, POE, modified reinforcing agent, modified light stabilizer and additives; through supercritical carbon dioxide assisted and vacuum devolatilization double screw extrusion granulation; and then through asymmetric temperature control injection molding of fixed mold quenching and movable mold slow cooling, an environmentally friendly material is obtained. The present application cooperates endogenous natural antioxidant and exogenous ultraviolet resistance, and the surface layer is dense and crystallized to block, and supercritical low temperature processing is used, so that the material has excellent weather resistance and mechanical properties.

[0006] To achieve the above objectives, the present invention provides the following technical solution: Unless otherwise specified, all the following parts are by weight.

[0007] This invention provides a method for preparing an environmentally friendly material for automotive interior and exterior trim, comprising the following steps: Add 60-70 parts of polypropylene (isotacticity ≥95%, melt index (MI) 18 g / 10 min) and 12 parts of ethylene-octene copolymer (octene content 25%, density 0.87 g / cm³). 3 14-18 parts of modified reinforcing agent, 1-2 parts of modified light stabilizer, 1 part of KH-550, 0.5 parts of nucleating agent NA-11 and 0.5 parts of EBS lubricant are added together into a high-speed mixer, the speed is set to 800 rpm and stirred for 5 minutes to obtain a mixture. The mixture is fed into a co-rotating parallel twin-screw extruder with a length-to-diameter ratio of L / D = 48:1 via the main feeder. The temperature range is set (gradient heating and low-temperature processing): Zone 1: 150-160℃; Zone 2: 160-170℃; Zone 3: 175℃; Zones 4 to 6: set at 180℃. In Zone 5, supercritical carbon dioxide is injected through a metering pump (pressure 15MPa, injection amount is 0.5% of the total material mass), and the main screw speed is set to 350rpm; Zone 7: 185℃; Zone 8: 190℃, with an atmospheric pressure exhaust port to allow most of the carbon dioxide gas in the system to slowly escape under atmospheric pressure; Zone 9: 190-200℃, with the vacuum pump turned on, and the vacuum degree reaches -0.098MPa; Zone 10: 190℃; an underwater pelletizer system is used, with the cooling water temperature set at 45℃. After pelleting, the pellets are dried by a centrifugal dehydrator to obtain composite masterbatch. The composite masterbatch is added to the injection molding machine, and the barrel temperature is set to 190℃-200℃. During injection, the water temperature on the fixed mold side (in contact with the outer surface of the product) is set to 20℃ (rapid cooling), and the water temperature on the moving mold side (in contact with the inner surface of the product) is set to 65℃ (slow cooling). At the same time, the injection pressure is set to 75-85MPa, the holding pressure is set to 60MPa, the holding time is set to 15s, and the cooling time is set to 25s. After molding and demolding, an environmentally friendly material is obtained.

[0008] Preferably, the preparation method of the modified reinforcing agent is as follows: 3-7 parts of alkali lignin (weight average molecular weight of 5000-8000) are slowly added to 100 parts of an alkaline aqueous solution with a pH of 12.5 (adjusted with a 5% sodium hydroxide aqueous solution by mass), and heated to 60°C and stirred until completely dissolved; then 10 parts of nanocellulose (average diameter of 10-50 nm, average length of 1-2 μm) are added, and the mixture is sheared at 10000 rpm for 30 min using a high-shear dispersing emulsifier to form a suspension; the pH of the system is adjusted to 7 using glacial acetic acid to make the alkali lignin... The precipitate is formed; the system temperature is raised to 70℃, and 1-2 parts of pre-hydrolyzed silane coupling agent KH-550 are added dropwise to the suspension (hydrolysis conditions: 1-2 parts of KH-550 are added to 15 parts of 90% ethanol aqueous solution, the pH is adjusted to 4 with glacial acetic acid, and the mixture is stirred at room temperature for 30 min). After the addition is complete, the mixture is stirred at a constant temperature of 70℃ for 2-4 h. The slurry after the reaction is sent to a spray dryer, the inlet air temperature is set to 160℃, the outlet air temperature is set to 80℃, and the atomizing disc speed is set to 15000 rpm to obtain the modified reinforcing agent (moisture content below 0.5%).

[0009] Preferably, the modified light stabilizer is prepared as follows: 0.1-2 parts of light stabilizer HALS-944 are dissolved in 20 parts of anhydrous ethanol and ultrasonically vibrated for 10 minutes until completely dissolved; 1-3 parts of mesoporous silica (SBA-15, with an average pore size of 7-8 nm) are added to the solution, and the mixture is placed in a vacuum drying oven at a temperature of 40°C. The vacuum is then drawn to a pressure of 0.08 MPa and maintained for 1-3 hours; after the vacuum is broken, the mixture is transferred to a rotary evaporator and rotary evaporated at a pressure of approximately 0.08 MPa, a water bath temperature of 60°C, and a rotation speed of 60 rpm to remove excess ethanol solvent. Finally, the mixture is dried in a vacuum oven at 80°C for 4 hours to obtain the modified light stabilizer.

[0010] Another aspect of the present invention provides an environmentally friendly material for automotive interior and exterior trim, the raw materials of which include polypropylene, ethylene-octene copolymer, modified reinforcing agent, modified light stabilizer, KH-550, nucleating agent NA-11 and EBS lubricant.

[0011] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention constructs a dual-effect chemical protection system combining endogenous antioxidant and exogenous UV protection, thereby improving the weather resistance of materials. Through hybrid modification of alkali lignin and nanocellulose, the antioxidant and UV absorption properties of the phenolic hydroxyl groups in the lignin molecular skeleton are utilized as a free radical quencher; simultaneously, the hindered amine light stabilizer HALS-944, loaded in mesoporous silica, is used as an exogenous UV protectant. The chemical synergy formed by these two components in the polypropylene matrix can effectively and continuously consume free radicals generated during photo-oxidative aging, effectively blocking the breakage reaction of polypropylene and plant fiber macromolecular chains. This solves the technical problem of the easy degradation of mechanical properties in traditional environmentally friendly composite materials under outdoor exposure or high-temperature environments inside vehicles.

[0012] This invention utilizes the synergistic effect of formulation nucleation and asymmetric temperature-controlled injection molding to construct a dense physical barrier on the outer surface of the material, resisting environmental aging. During the injection molding process, by controlling the temperature difference between the stationary mold side (rapid cooling at 20°C) and the moving mold side (slow cooling at 65°C), combined with the heterogeneous induced crystallization effect of the nucleating agent NA-11 added to the formulation, a dense microcrystalline skin layer is forced to form on the outer surface of the automotive interior and exterior parts by the polypropylene melt. This robust, dense skin layer physically isolates the material from the penetration of ultraviolet rays and oxidizing agents, thus improving weather resistance.

[0013] In this invention, the injection of supercritical carbon dioxide acts as a plasticizer and viscosity reducer, lowering the extrusion processing temperature to 180°C. This prevents alkali lignin and nanocellulose from undergoing thermal degradation and discoloration under conventional high-temperature, high-shear conditions, thus preserving their natural weather-resistant activity to the greatest extent. Furthermore, the light stabilizer is pre-loaded into mesoporous silica SBA-15. The mesoporous channels not only capture and lock in a large amount of VOCs generated during the vacuum devolatilization stage but also play a slow-release role during the long-term service life of the material. This effectively prevents the rapid migration and precipitation of small-molecule stabilizers to the outer surface, giving automotive interior and exterior parts a longer lifespan. Attached Figure Description

[0014] Figure 1 The tensile strength retention rate and notched impact strength retention rate after thermo-oxidative aging in Examples 1-5 of this invention. Detailed Implementation

[0015] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] For details, please refer to [link / reference]. Figure 1This invention provides an environmentally friendly material for automotive interior and exterior trim, and a method for preparing the same. The technical solution is as follows: Example 1 Five parts of alkali lignin were slowly added to 100 parts of an alkaline aqueous solution with a pH of 12.5, and the mixture was heated to 60°C and stirred until completely dissolved. Then, 10 parts of nanocellulose were added, and the mixture was sheared at 10,000 rpm for 30 minutes using a high-shear dispersing emulsifier to form a suspension. The pH of the system was adjusted to 7 with glacial acetic acid to precipitate the alkali lignin. The system temperature was raised to 70°C, and 1.5 parts of pre-hydrolyzed silane coupling agent KH-550 were added dropwise to the suspension (hydrolysis conditions: 1.5 parts of KH-550 were added to 15 parts of a 90% ethanol aqueous solution, the pH was adjusted to 4 with glacial acetic acid, and the mixture was stirred at room temperature for 30 minutes). After the addition was complete, the mixture was stirred at a constant temperature of 70°C for 3 hours. The resulting slurry was then fed into a spray dryer with an inlet air temperature of 160°C, an outlet air temperature of 80°C, and a spray disc speed of 15,000 rpm to obtain the modified reinforcing agent (moisture content below 0.5%).

[0017] One part of light stabilizer HALS-944 was dissolved in 20 parts of anhydrous ethanol and ultrasonically vibrated for 10 min until completely dissolved. Two parts of mesoporous silica (SBA-15) were added to the solution, and the mixture was placed in a vacuum drying oven at 40°C. The vacuum was evacuated to a degree of 0.08 MPa and maintained for 2 h. After the vacuum was broken, the mixture was transferred to a rotary evaporator and the excess ethanol solvent was removed by rotary evaporation at a vacuum of approximately 0.08 MPa, a water bath temperature of 60°C, and a rotation speed of 60 rpm. Finally, the mixture was dried in a vacuum oven at 80°C for 4 h to obtain the modified light stabilizer.

[0018] 65 parts of polypropylene, 12 parts of ethylene-octene copolymer, 16 parts of modified reinforcing agent, 1.5 parts of modified light stabilizer, 1 part of KH-550, 0.5 parts of nucleating agent NA-11 and 0.5 parts of EBS lubricant were put into a high-speed mixer, the speed was set to 800 rpm and stirred for 5 minutes to obtain a mixture. The mixture is fed into a co-rotating parallel twin-screw extruder with a length-to-diameter ratio of L / D = 48:1 via the main feeder. The temperature range is set (gradient heating and low-temperature processing): Zone 1: 155℃; Zone 2: 165℃; Zone 3: 175℃; Zones 4 to 6: set at 180℃. In Zone 5, supercritical carbon dioxide is injected via a metering pump (pressure 15MPa, injection amount is 0.5% of the total material mass), and the main screw speed is set to 350rpm; Zone 7: 185℃; Zone 8: 190℃; Zone 9: 195℃, the vacuum pump is turned on, and the vacuum degree reaches -0.098MPa; Zone 10: 190℃; an underwater pelletizer system is used, and the cooling water temperature is set to 45℃. After pelleting, the pellets are dried by a centrifugal dehydrator to obtain composite masterbatch. The composite masterbatch is added to the injection molding machine, and the barrel temperature is set to 195℃. During injection, the water temperature on the fixed mold side (in contact with the outer surface of the product) is set to 20℃ (rapid cooling), and the water temperature on the moving mold side (in contact with the inner surface of the product) is set to 65℃ (slow cooling). At the same time, the injection pressure is set to 80MPa, the holding pressure is set to 60MPa, the holding time is set to 15s, and the cooling time is set to 25s. After molding and demolding, an environmentally friendly material is obtained.

[0019] Examples 2-5 refer to the parameter conditions in Example 1, with specific differences shown in Table 1.

[0020] Table 1 Parameters and conditions for Examples 1-5 Dosage of natural lignin / parts 5 3 4 6 7 Dosage of KH-550 / parts 1.5 1 1 2 2 Time of stirring reaction / h 3 2 2.5 3.5 4 Dosage of HALS-944 / parts 1 0.1 0.5 1.5 2 Dosage of mesoporous silica / parts 2 1 3 1 3 Time of vacuum holding / h 2 1 1.5 2.5 3 Dosage of polypropylene / parts 65 60 62 68 70 Dosage of modified reinforcing agent / parts 16 14 15 17 18 Dosage of modified light stabilizer / parts 1.5 1 2 2 1 Temperature of zone 1 / °C 155 150 150 160 160 Temperature of zone 2 / °C 165 160 170 160 170 Temperature of zone 9 / °C 195 190 200 200 190 Temperature of barrel / °C 195 200 200 190 190 Pressure of injection / MPa 80 75 85 85 75 Comparative Example 1: The parameters and conditions in Example 1 were the same, except that no natural lignin was added when preparing the modifier and reinforcing agent. Instead, an equal amount of nanocellulose and KH-550 were used for modification.

[0021] Comparative Example 2 follows the same parameters and conditions as in Example 1, except that no modified light stabilizer is prepared, and equal amounts of light stabilizer HALS-944 are directly physically mixed with the matrix resin in a high-speed mixer.

[0022] Comparative Example 3 follows the same parameters and conditions as in Example 1, except that no separate modifier is prepared. Instead, untreated natural lignin, nanocellulose, matrix resin, and KH-550 are directly fed into a twin-screw extruder for simple physical blending.

[0023] Comparative Example 4 follows the same parameters as in Example 1, except that the supercritical carbon dioxide injection pump is turned off during the twin-screw extrusion process.

[0024] Comparative Example 5 uses the same parameters as in Example 1, except that in the injection molding process, the water temperature on both the fixed mold side and the moving mold side is set to room temperature (45°C), and the asymmetric temperature control technology of 20°C rapid cooling / 65°C slow cooling is not used.

[0025] Comparative Example 6 follows the same parameters and conditions as in Example 1, except that nucleating agent NA-11 is not added.

[0026] Comparative Example 7 follows the same parameters and conditions as in Example 1, except that the hindered amine light stabilizer HALS-944 is not added (mesoporous silica SBA-15 is still retained).

[0027] Experimental Example 1: Mechanical Property Testing Following ISO 527-2 standard, dumbbell-shaped test specimens were fabricated from environmentally friendly materials using an injection molding machine. Tensile tests were then conducted on Examples 1-5 and Comparative Examples 1-7 using a Zwickau Roell Z020 universal testing machine. Notched impact strength tests were performed on Examples 1-5 and Comparative Examples 1-7 according to ISO 180 standard. The results are shown in Table 2.

[0028] Table 2 Mechanical properties of Examples 1-5 and Comparative Examples 1-7 Example 1 31.2 43.8 Example 2 31.1 43.5 Example 3 31.5 44.2 Example 4 30.9 43.6 Example 5 30.8 43.1 Comparative Example 1 29.5 35.6 Comparative Example 2 30.1 41.2 Comparative Example 3 24.3 21.5 Comparative Example 4 27.8 32.4 Comparative Example 5 29.8 38.5 Comparative Example 6 28.5 37.2 Comparative Example 7 31.2 43.2 Table 2 shows that, compared to Example 1, the notched impact strength of Comparative Example 1 decreased significantly. This is because natural lignin is not only an antioxidant, but it also physically entangles with nanocellulose in the aqueous phase, forming a hybrid network with a certain degree of flexibility and steric hindrance. Without lignin, single nanocellulose is prone to local micro-agglomeration in the polypropylene matrix and cannot form a multi-level interlayer interlocking structure with the ethylene-octene copolymer, resulting in reduced efficiency in absorbing strain energy during impact and weakened toughness. The initial mechanical properties of Comparative Example 2 decreased slightly. Although the direct physical mixing of HALS-944 did not drastically affect the initial tensile and impact properties of the material, the lack of the reinforcing effect of mesoporous silica (SBA-15), a nanoscale rigid inorganic particle, weakened the rigid support framework of the system. Furthermore, the small molecule HALS, directly free in the matrix, easily exhibited uneven distribution during high-mixing extrusion, even playing a negative plasticizing role, leading to a slight decrease in tensile strength. The mechanical properties of Comparative Example 3 showed a precipitous decline. This is because natural lignin and nanocellulose contain a large number of polar hydroxyl groups, resulting in extremely poor compatibility with non-polar polypropylene melt. Without high-shear dispersion in an aqueous phase and in-situ grafting modification with silane coupling agent KH-550, these plant-based fillers formed severe macroscopic agglomerates in the extruder. These agglomerates became stress concentration points prone to crack initiation under stress, leading to interfacial debonding and significant brittle fracture of the material. Comparative Example 4 showed a significant deterioration in mechanical properties after the supercritical carbon dioxide injection was shut off. The viscosity-reducing and lubricating effects of the supercritical fluid were lost, and the viscosity of the polypropylene melt remained extremely high at 180°C. The strong shear friction during twin-screw extrusion generated excessively high local temperatures. This not only caused partial thermal degradation (carbonization) of nanocellulose and lignin, destroying their reinforcing skeleton, but also hindered the uniform dispersion of fillers in the matrix. The thermal degradation products became internal defects in the material, significantly reducing the overall mechanical properties of the composite material.

[0029] The notched impact strength of Comparative Example 5 decreased compared to Example 1. Asymmetric temperature control (20°C for fixed mold / 65°C for moving mold) not only constructs a weather-resistant physical barrier, but the resulting core-skin structure also provides external rigidity and internal toughness. When using conventional uniform temperature injection molding at 45°C, a highly crystalline, dense skin layer cannot be formed quickly on the surface, resulting in more micropores and amorphous morphology on the material surface. This increases notch sensitivity, making it more prone to cracking from surface micro-defects when resisting external impacts. Comparative Example 6 showed a significant decrease in both tensile strength and impact strength. The nucleating agent NA-11 played a crucial role in heterogeneous nucleation in the system, promoting rapid and orderly crystallization of polypropylene molecular chains, forming a fine and uniform spherulite structure. Without NA-11, the crystallinity of polypropylene decreased, and the spherulite size became larger and less uniform. The decrease in crystallinity directly led to a loss of material rigidity (tensile strength); simultaneously, the coarse grains easily caused stress concentration at the interface, preventing the toughening phase (POE) from effectively transferring and dispersing stress, thus weakening the impact toughness. The initial mechanical properties of Comparative Example 7 are very close to those of Example 1. This is because HALS-944, as a chemical anti-aging additive, plays a core role in providing long-term weather protection during the later stages of material service, rather than physical reinforcement of the initial structure.

[0030] Experiment Example 2 Weather Resistance Test Referring to GB / T 7141-2008 standard, standard dumbbell-shaped specimens and notched impact specimens prepared using an injection molding machine were placed in a hot air aging test chamber. The test temperature was set at 120℃, and the aging time was 1000h. After the test, the specimens were removed and conditioned for 24h in a standard environment of 23℃ and 50% relative humidity. Subsequently, the tensile strength and notched impact strength of Examples 1-5 and Comparative Examples 1-7 were tested, and the performance retention rate after aging was calculated. Referring to GB / T 16422.3 standard, a QUV accelerated ultraviolet aging tester was used for testing. The light source was a UVA-340 fluorescent ultraviolet lamp, and the irradiance was set at 0.76W / (m²·nm) (at 340nm). The light / condensation cycle was set as follows: 8h light (60℃) + 4h condensation (50℃), with a total test time of 1000h. After aging, the tensile strength and notched impact strength of Examples 1-5 and Comparative Examples 1-7 were tested. The results are shown in Table 3. The tensile strength retention rate and notched impact strength retention rate after thermo-oxidative aging in Examples 1-5 are as follows: Figure 1 As shown.

[0031] Table 3 Weather resistance of Examples 1-5 and Comparative Examples 1-7 Example 1 92.8 90.5 93.1 90.9 Example 2 92.5 90.2 92.8 90.5 Example 3 93.1 90.8 93.5 91.2 Example 4 92.2 89.9 92.4 90.2 Example 5 92.6 90.3 92.9 90.6 Comparative Example 1 76.5 72.8 74.2 69.5 Comparative Example 2 83.2 79.5 78.4 74.1 Comparative Example 3 65.4 58.9 63.2 55.4 Comparative Example 4 73.8 69.2 72.5 67.8 Comparative Example 5 79.5 75.3 77.8 73.6 Comparative Example 6 81.2 76.8 79.4 75.2 Comparative Example 7 84.5 81.2 68.3 62.4 From Table 3 and Figure 1It can be observed that, in Comparative Example 1, the absence of natural lignin resulted in a comprehensive and significant decline in the material's thermo-oxidative and UV aging retention rates. Under prolonged exposure to ultraviolet light at 120°C, the polypropylene matrix and nanocellulose readily generated large molecular free radicals, leading to chain breakage. Due to the lack of abundant phenolic hydroxyl groups in the lignin molecules as endogenous antioxidants to continuously quench these free radicals, simply relying on a small amount of added light stabilizer was insufficient to block the degradation of deep molecular chains, resulting in severe embrittlement of the material. In Comparative Example 2, after a 1000-hour aging cycle, the performance degradation was significantly greater than in the Example 1, especially the UV aging retention rate. This is because the free small molecule HALS-944 easily migrated to the material surface and precipitated (frost formation) in the alternating environment of high temperature and light condensation, or was prematurely consumed. The lack of the long-term sustained-release effect of mesoporous silica (SBA-15) channels resulted in a gap in UV protection during the later stages of aging, failing to provide durable weather protection. Comparative Example 3 exhibited extremely poor performance after aging. Due to direct physical mixing, the filler agglomerated severely, resulting in numerous microcracks and pores at the interface. Under a 1000-hour thermo-oxidative and ultraviolet (accompanied by condensate erosion) environment, oxygen and moisture penetrated along these interface defects, triggering three-dimensional oxidative degradation from the inside out. Stress concentration points rapidly evolved into macroscopic cracks after aging, leading to a complete collapse of mechanical properties. Comparative Example 4 showed extremely low weather resistance retention. Because supercritical fluid cooling and viscosity reduction were not introduced during processing, the high temperature (205℃) and strong shear force in the extruder prematurely destroyed the antioxidant active groups such as phenolic hydroxyl groups of lignin, while also causing thermo-oxidative degradation of nanocellulose. This is equivalent to the material prematurely aging before leaving the factory, losing its own anti-aging ability, and therefore unable to resist environmental erosion in the subsequent 1000-hour harsh aging test.

[0032] Comparative Example 5 did not employ an asymmetric rapid cooling temperature control process, resulting in the inability to form a high-density crystalline skin on the material surface. This loose surface layer could not effectively block the penetration of high-temperature oxygen, ultraviolet rays, and moisture into the material's interior. Environmental media easily penetrated the surface layer, accelerating the oxidation and photodegradation of the deep structure within the matrix, causing a decrease of more than ten percentage points in both thermo-oxidative and ultraviolet aging retention rates. The degradation mechanism of Comparative Example 6 was similar to that of Comparative Example 5, but because it still retained the cold mold temperature, a skin of a certain thickness but low crystallinity was formed on its surface. Due to the lack of NA-11-induced formation of a regular and compact spherulite physical barrier, the blocking efficiency of ultraviolet rays and oxygen was greatly reduced. Under long-term ultraviolet irradiation, the surface was the first to pulverize, and microcracks subsequently propagated inward, leading to a decrease in the overall mechanical property retention rate. Comparative Example 7 performed reasonably well in thermo-oxidative aging, but its UV aging retention rate dropped precipitously, which fully demonstrates the indispensability of the dual-effect protection system of endogenous lignin and exogenous hindered amine. Faced with strong ultraviolet radiation for up to 1000 hours, lignin alone cannot capture all high-energy photoinduced free radicals in time. Without HALS-944, the polypropylene macromolecular chain is quickly cut off by ultraviolet radiation, resulting in severe damage to its impact resistance.

[0033] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an environmentally friendly material for automotive interior and exterior trim, characterized in that, Includes the following steps: Polypropylene, ethylene-octene copolymer, modified reinforcing agent, modified light stabilizer and additives are mixed to obtain a mixture; the mixture is granulated by twin-screw extrusion with supercritical carbon dioxide assistance and vacuum devolatilization to obtain a composite masterbatch; the composite masterbatch is subjected to asymmetric temperature-controlled injection molding to obtain the environmentally friendly material; the modified reinforcing agent is obtained by surface coupling modification of a hybrid composed of alkali lignin and nanocellulose by KH-550. The modified light stabilizer is obtained by loading and modifying a hindered amine light stabilizer with mesoporous silica.

2. The method for preparing an environmentally friendly material for automotive interior and exterior decoration according to claim 1, characterized in that, The preparation method of the mixture is as follows: the polypropylene, the ethylene-octene copolymer, the modified reinforcing agent, the modified light stabilizer, KH-550, the nucleating agent and EBS lubricant are put into a high-speed mixer and stirred to obtain the mixture.

3. The method for preparing an environmentally friendly material for automotive interior and exterior decoration according to claim 1, characterized in that, The preparation method of the composite masterbatch is as follows: the mixture is fed into a twin-screw extruder through a main feeder, zone 1: 150-160℃; zone 2: 160-170℃; zone 3: 175℃; zones 4 to 6: 180℃; supercritical carbon dioxide is injected in zone 5 through a metering pump; zone 7: 185℃; zone 8: 190℃; and an atmospheric pressure exhaust port is set. Zone 9: 190-200℃, vacuum pump turned on; Zone 10: 190℃; underwater pelletizer system is used, and after pelletizing, the composite masterbatch is dried by centrifugal dehydrator.

4. The method for preparing an environmentally friendly material for automotive interior and exterior trim according to claim 1, characterized in that, The preparation method of the environmentally friendly material is as follows: the composite masterbatch is added to the injection molding machine, the barrel temperature is set to 190℃-200℃, the water temperature on the fixed mold side is set to 20℃ and the water temperature on the moving mold side is set to 65℃ during injection molding, and the injection pressure is set to 75-85MPa. After molding and demolding, the environmentally friendly material is obtained.

5. The method for preparing an environmentally friendly material for automotive interior and exterior decoration according to claim 1, characterized in that, The preparation method of the modified reinforcing agent is as follows: the alkali lignin is added to an alkaline aqueous solution, dissolved, and then the nanocellulose is added and sheared to form a suspension; the pH value of the system is adjusted to 7 with glacial acetic acid; the pre-hydrolyzed KH-550 is added dropwise to the suspension, and after the addition is complete, the mixture is stirred for 2-4 hours; the slurry after the reaction is sent to a spray dryer to obtain the modified reinforcing agent.

6. The method for preparing an environmentally friendly material for automotive interior and exterior decoration according to claim 1, characterized in that, The modified light stabilizer is prepared by dissolving the light stabilizer HALS-944 in anhydrous ethanol, ultrasonically dissolving it, adding the mesoporous silica to the solution, placing the mixture in a vacuum drying oven for 1-3 hours, breaking the vacuum, transferring it to a rotary evaporator, removing excess ethanol solvent by rotary evaporation, and vacuum drying to obtain the modified light stabilizer.

7. An environmentally friendly material for automotive interior and exterior trim, characterized in that, The raw materials for synthesizing the environmentally friendly material include polypropylene, ethylene-octene copolymer, modified reinforcing agent, modified light stabilizer, KH-550, nucleating agent NA-11, and EBS lubricant; the environmentally friendly material is prepared by the preparation method according to any one of claims 1-6.